Supporting research students - Allan, Barbara 1954- (London Facet, 2010)
This volume offers guidance to LIS professionals to enable them to support the specialist needs of research students effectively. The key areas covered include the world of research and research students, styles of research, skills required by research students and the rise of the virtual graduate school.
1. Introduction -- Structure of this book, Introduction to the world of research and research students, The production and dissemination of knowledge, Types of research degree, Stakeholders in research degrees, Contemporary issues regarding supporting research students, Summary 2. Research and the research process -- Research proposal, Research approach and methods, Data collection and analysis, Access and ethical issues, Summarizing the research process, Research issues, Writing up, The complexity of the research process, Summary 3. The research student's experience -- Introduction, Starting points, Induction, Working with a supervisor, Getting started on the doctorate, Selecting a topic, Developing the study, Summary 4. Moving forward and completing the research -- Introduction, Moving forward, Methodology, Fieldwork, Writing up,Viva voce examination, Amendments and completion, Summary 5. Research skills training -- Introduction, Training and skills of research students, The UK Research Councils' Joint Statement of training requirements for research students, Skills development, Library and information research skills, Case study: Use of information sources, Summary 6. Supporting research students in academic libraries and information services -- Introduction, Information needs , Current approaches to supporting research students, Case Study: Example session plan -- introduction to referencing,Case Study: MI512 research training course for PhD students, Targeting and communicating with research students , Self-assessment: how do you support research students?, Summary 7. Virtual graduate schools -- Introduction, The development of virtual graduate schools,Case Study: University of Hull Virtual Graduate School and the Graduate Virtual Research Environment, Other approaches to developing a virtual graduate school, Implications for library and information workers, Summary 8. Introduction to research communities -- Introduction, What are communities?, Research communities, Information sharing in academic communities, Professional associations,Academic conferences, Online networking, Implications for library and information workers, Summary, Notes 9. Professional development -- Introduction, Professional organizations and networks, Development offered by higher education institutions, Research degrees
Keywords: Academic libraries -- Services to graduate students